2015
DOI: 10.1097/mca.0000000000000235
|View full text |Cite
|
Sign up to set email alerts
|

Impact of increased admission lipid levels on periprocedural myocardial injury following an elective percutaneous coronary intervention

Abstract: The present study indicates that increased preprocedural TC, LDL-C, and TG serum levels are associated with PMI and its severity following elective PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Li et al found that the low preprocedural LDL-C levels were correlated with lower risk of PMI in PCI patients, and the risk of postprocedural cTnI elevation was increased by 12% to 20% due to increased 1-SD in LDL-C [ 13 ]. Similarly, Buturak et al also observed a direct connection between preprocedural LDL-C levels and PMI in PCI patient with stable angina pectoris [ 18 ]. A cohort study that enrolled 302 consecutive patients reported that the ratios of LDL-C to high-density lipoprotein cholesterol (LDL-C/HDL-C) were significantly associated with PMI following elective PCI [ 19 ].…”
Section: Discussionmentioning
confidence: 96%
“…Li et al found that the low preprocedural LDL-C levels were correlated with lower risk of PMI in PCI patients, and the risk of postprocedural cTnI elevation was increased by 12% to 20% due to increased 1-SD in LDL-C [ 13 ]. Similarly, Buturak et al also observed a direct connection between preprocedural LDL-C levels and PMI in PCI patient with stable angina pectoris [ 18 ]. A cohort study that enrolled 302 consecutive patients reported that the ratios of LDL-C to high-density lipoprotein cholesterol (LDL-C/HDL-C) were significantly associated with PMI following elective PCI [ 19 ].…”
Section: Discussionmentioning
confidence: 96%
“…7 Buturak et al also demonstrated that the concentrations of preprocedural LDL-C were positively related to PMI in PCI patients. 18 Experimental evidences had confirmed that non-HDL-C is a strong predictor for cardiovascular disease risk assessment. 19,20 Li et al and Maadani et al 7,21 previously confirmed that low non-HDL-C concentrations were associated with less risk of PMI in CAD patients and was higher in PMI patients after PCI.…”
Section: Discussionmentioning
confidence: 98%
“…Type 4a MI was defined as elevation of hscTnT values greater than five times the 99 th percentile URL in patients with normal baseline values (≤99 th percentile URL) or a rise of hscTnT values >20% if the baseline values are elevated and are stable or falling in addition to clinical and/or laboratory findings indicative of myocardial ischemia ( 25 ). PMI was defined as previously described ( 2 , 7 9 ). Accordingly, after exclusion of patients with elevated baseline troponin values, we categorized the participants into three groups based on post-procedural serum hscTnT concentrations:…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, clinical and procedural factors that may lead to PMI have been investigated to improve clinical outcomes in patients undergoing elective PCI. Although periprocedural side branch occlusion, coronary dissection, distal embolization, and no-reflow during stenting are well known factors to be related to PMI, actual data also indicate that metabolic status of the patient such as admission dyslipidemia, abnormal glucose levels, and albuminuria are associated with PMI in patients undergoing elective PCI ( 6 9 ).…”
Section: Introductionmentioning
confidence: 99%